2007
DOI: 10.1017/s0033291707001687
|View full text |Cite
|
Sign up to set email alerts
|

COPD education and cognitive behavioral therapy group treatment for clinically significant symptoms of depression and anxiety in COPD patients: a randomized controlled trial

Abstract: CBT group treatment and COPD education can achieve sustainable improvements in QoL for COPD patients experiencing moderate-to-severe symptoms of depression or anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(172 citation statements)
references
References 58 publications
3
156
1
12
Order By: Relevance
“…In line with these findings, a recent meta-analysis revealed only small, nonsignificant effects of CBT on self-reported symptoms of depression in COPD patients [63]. In comparison to COPD education, CBT has been shown to have a comparable antidepressant effect [64].…”
Section: Effects Of Psychotherapymentioning
confidence: 83%
“…In line with these findings, a recent meta-analysis revealed only small, nonsignificant effects of CBT on self-reported symptoms of depression in COPD patients [63]. In comparison to COPD education, CBT has been shown to have a comparable antidepressant effect [64].…”
Section: Effects Of Psychotherapymentioning
confidence: 83%
“…31 Simon and colleagues observed that persons who started antidepressant treatment in primary care experienced significant improvement in depression as well as function and disability. 32 The reduction in disability following depression treatment was as great in those with multimorbidity as in those without medical conditions. Although antidepressants are effective for treating depression in patients with a wide range of physical diseases, antidepressants do not reliably affect disease self-management behaviors in chronically ill patients, 31 which suggests the potential benefits of educational and psychosocial treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapy added to pulmonary rehabilitation significantly reduces depression in COPD patients [137]. Cognitive behavioural therapy also improves the quality of life in COPD patients with depression [138]. Finally, if depression is caused by systemic inflammation then treating lung inflammation or systemic anti-inflammatory treatments should also be effective and depression needs to be measured in controlled trials in COPD patients once these drugs are in large clinical trials.…”
Section: Treatmentmentioning
confidence: 99%